The Application of Functional Magnetic Resonance Imaging in Type 2 Diabetes Rats With Contrast-Induced Acute Kidney Injury and the Associated Innate Immune Response - Li, Yanfei; Shi, Dafa; Zhang, Haoran; Yao, Xiang; Wang, Siyuan; Wang, Rui; Ren, Ke (Frontiers in Physiology, 2021)
Abstract Aims/hypothesis：Contrast-induced acute kidney injury (CI-AKI) is the third most common in-hospital acquired AKI and its mechanism is not fully clear. Its morbidity increases among populations with chronic kidney disease (CKD), senior age, diabetes mellitus (DM), and so on. Since lack of immediate and effective noninvasive diagnosing way, CI-AKI often prolongs hospital stays and increase extra medical cost. This study aims to explore the possibility of diagnosing CI-AKI with functional magnetic resonance imaging (fMRI) based on type 2 DM rats. In the meanwhile, we attempt to reveal the immune response in CI-AKI and to answer why DM is a predisposing factor for CI-AKI. Methods: The type 2 DM rats were established by feeding high-fat and high-sugar diet combined with streptozotocin (STZ) injection. Iodixanol 320 was the contrast medium (CM) administered to rats. Images were obtained with a SIEMENS Skyra 3.0T magnetic resonance imager. Renal histopathological evaluation was accompolished with H&E staining and immunohistochemistry (IHC). The innate immune response was revealed through western blotting and flow cytometry. Results：Blood oxygenation level-dependent (BOLD) imaging and intravoxel incoherent motion (IVIM) imaging can be used to predict and diagnose CI-AKI effectively. R2* value (r＞0.6, p＜0.0001) and D value (|r|＞0.5, p＜0.0001) have great correlation with histopathological scores respectively. NOD-like receptor pyrin 3 (NLRP3) inflammasome participates in CI-AKI and exacerbate CI-AKI in DM rats. Moreover, the numbers of neutrophils and M1 macrophages increase dramatically in rat kidneys after CM injection (the number of neutrophils from 56.3% to 56.6% and M1 macrophages from 48% to 54.1% in normal rats, the number of neutrophils from 85.5% to 92.4% and M1 macrophages from 82.1% to 89.8% in DM rats). Conclusions/interpretation: BOLD and IVIM-D can be an effective non-invasive tool in predicting CI-AKI. Innate immune response takes effect in the progress of CI-AKI and DM will exacerbate this progress.